Mokslinės-techninės informacijos sistemos – kaip sudėtingos sistemos - Broniukaitis, Romualdas (Knygotyra, 1987)
Scientific and technical information systems are analysed as complex systems, the structure of which is determined by principles of their functioning and peculiarities of problems under consideration. Characteristic data of quality of scientific and technical information system functioning are determined, methods of their evaluation are presented.